O jornal Correio Braziliense no processo de constru????o da cultura de Bras??lia: das origens ao dia 21 de abril de 1961 - Rocha, Marcella Godoy Evangelista da (2016)
This study aims to identify the forms which the newspaper Correio Braziliense contributed to the formation of Brasilia???s cultural identity during the first year after its opening (April 21, 1960 to April 21, 1961). The newspaper???s first edition was published on the same day the city was inaugurated. This research was carried out at Brasilia???s Documentation Center of Associated Journals ??? CEDOC, and aims to analyze and identify issues related to events that happened in the city during it???s first year as the new capital of Brazil. Initially, the newspaper???s story was considered, since its founding by Hip??lito Jos?? da Costa in London, in the nineteenth century, until its revival in Brasilia. The newspaper's structure (the only printed media in Brasilia during this period), its contribution to the formation of the cultural identity of the city, the customs and routines acquired by the pioneers of the city, were also analyzed in this research. To this end, interviews were conducted with pioneers considering their relationship with the newspaper at the time. Finally, the categories used for the establishment and corpus analysis were: Cultural, religious, leisure and entertainment activities; Trade and services in general - including radio and TV programming; Education and Sport. As a result of the research, we identified that culture can hardly be categorized and that a complex design of the cultural process is best suited to the objectives of the work. We therefore appealed to Edgar Morin???s (2005) perception on culture in order to understand the process of feedback between the newspaper and the life in the city in the cultural formation of Brasilia.